Concha bullosa, nasal septal deviation, and their impacts on maxillary sinus volume among Emirati people: A cone-beam computed tomography study - Natheer Al‐Rawi; Asmaa T. Uthman; Elaf Abdulhameed; Ahmed Sameer Al Nuaimi; Zahra Seraj (2019)
To determine the prevalence of concha bullosa (CB) and nasal septal deviation (NSD) and their impact on maxillary sinus volume (MSV).Cone-beam computed tomographic (CBCT) images of 106 Emirati people were used in this study. The direction and angle of septal deviation were calculated. The presence of CB, which could be unilateral, contralateral, or bilateral in relation to the direction of NSD, was also recorded. MSV was measured using reconstructed Digital Imaging and Communication in Medicine images on Dolphin 3D imaging software version 11.8 premium (Dolphin Imaging, Chatsworth, CA, USA). P values <0.05 were considered to indicate statistical significance.CB was detected in 37.7% of the sample; 20.7% of the sample showed single unilateral CB and 16.6% had single bilateral CB. NSD was seen in 74.5% of the sample. In the participants with CB, 45.5% showed mild deviation, 34.4% showed moderate deviation, and only 12.5% showed severe septal deviation. CB, but not NSD, was associated with significantly higher MSV on the affected side (P=0.001).Although NSD was observed in more than two-thirds of the sample and CB was present in more than one-third of the sample, only CB had a significant impact on MSV.